Manajemen Risiko Bisnis Ikan Pindang Perspektif Etika Bisnis Islam - Mohammad Alief Hidayatullah; Dwi Firlana Rosa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Risk management in the pindang fish business is very important to maintain business stability and increase consumer confidence. This study aims to analyze the application of risk management in the distribution of pindang fish in Bondowoso Regency based on the perspective of Islamic business ethics. Using a descriptive qualitative approach with a case study method, this research collected data through in-depth interviews, direct observation, and documentation. The analysis technique used is the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing.The results show that the application of Islamic business ethics principles such as honesty (shiddiq), responsibility (amanah), and justice ('adl) in risk management can improve distribution transparency. Traders who apply the principle of trustworthiness are better able to maintain product quality and fair prices, thereby increasing consumer satisfaction. In addition, the Islamic business ethics approach helps prevent the practice of quality manipulation and price discrepancies, which are often challenges in pindang fish distribution.The conclusion of this study confirms that the integration of Islamic values in distribution risk management not only improves business sustainability but also strengthens long-term relationships with consumers. The study recommends the implementation of stricter sharia-based distribution policies as well as the utilization of technology in the distribution system to improve efficiency and transparency